MULTIMEDIA AND ITS EFFECT ON THE QUALITY OF ENGLISH LANGUAGE TEACHING - Abbas Pourhosein Gilakjani; Seyedeh Mahsoumeh Ahmadi (Soegijapranata Catholic University, 2011)
One of the most important uses of technology is that it makes it easy for instructors to incorporate multimedia into their teaching. There are different multimedia tools. Three of the most popular ones are visual, auditory, and kinaesthetic in which students take in information. Some students are visual learners, while others are auditory or kinaesthetic learners. While students use all of their senses to take in information, they seem to have preferences in how they learn best. In order to help students learn, teachers need to teach as many of these preferences as possible. Therefore, teachers can incorporate these multimedia tools in their curriculum activities so that students are able to succeed in their classes. This study is an analysis of multimedia tools for Iranian EFL students. Over 100 students complete a questionnaire to determine if their multimedia tools are auditory, visual, or kinaesthetic. The purpose of this study is to increase faculty awareness and understanding of the impact of multimedia tools on the teaching process. A review of the literature along with analysis of the data will determine how multimedia tools affect the teachingprocess.